EFEKTIVITAS MODEL PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK DI SDN TENGKI 01 - Najma Alkhayya; Sunarsih, Diah; Laelia Nurpratiwiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effectiveness of the Scramble learning model on students' learning outcomes and critical thinking skills in mathematics learning at SDN Tengki 01. This research employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The population consisted of all fourth-grade students of SDN Tengki 01, totaling 33 students. The sampling technique used was saturated sampling, involving 15 students in the experimental class and 18 students in the control class. Data were collected through learning outcome tests and critical thinking observation sheets. Data analysis included normality tests, homogeneity tests, and Independent Sample t-Tests using SPSS version 22. The results showed that the significance value for learning outcomes was 0.008 (<0.05), indicating a significant difference between the experimental and control classes. Furthermore, the significance value for critical thinking skills was 0.000 (<0.05), indicating a significant difference between the two groups. These findings demonstrate that the Scramble learning model has a significant effect on improving students' learning outcomes and critical thinking skills. Therefore, the Scramble learning model can be used as an alternative learning strategy to create active, engaging, and meaningful learning experiences in elementary schools.